What Does an Engineer Do? - Owen, Ruth, 1967-; Wood, Alix (Buffalo, New York : Windmill Books, 2025)
Exploring the science behind the jobs! Young readers can discover how science is used by Engineers every day in their jobs.
Keywords: Engineers -- Juvenile literature; Science -- Juvenile literature